2008
DOI: 10.1002/glia.20816
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle inhibition attenuates microglial proliferation and production of IL‐1β, MIP‐1α, and NO after focal cerebral ischemia in the rat

Abstract: We recently showed that suppressing cell cycle progression inhibited reactive astrogliosis and promoted neuronal survival in an acute focal cerebral ischemia rat model. However, it remains unclear whether and to what extent the beneficial effects of cell cycle inhibition might also be attributed to the inhibition of microglial proliferation and cytokine/chemokine production. In this study, we showed that application of the cell cycle inhibitor roscovitine before middle carotid artery occlusion (MCAO) in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…In our previous study, we found that high glucose induced cyclin B1 expression in neurons [11]. It has been reported that the expression of cyclin A, cyclin B, and cyclin E was increased in glial cells in ischemia brain [36]. In the present study, we found that cyclin B1 was upregulated in OGD/R treated neurons, which means that the increased expression of cyclin B1 plays an important role in mediating neuronal cells re-entering cell cycle.…”
Section: Discussionsupporting
confidence: 63%
“…In our previous study, we found that high glucose induced cyclin B1 expression in neurons [11]. It has been reported that the expression of cyclin A, cyclin B, and cyclin E was increased in glial cells in ischemia brain [36]. In the present study, we found that cyclin B1 was upregulated in OGD/R treated neurons, which means that the increased expression of cyclin B1 plays an important role in mediating neuronal cells re-entering cell cycle.…”
Section: Discussionsupporting
confidence: 63%
“…20,21 Microglia activation manifests morphology change into an amoeboid shape, increased phagocytosis, and release of cytokines. 22,23 Our in vivo study exhibited that ICV injection of lentiviral-overexpressed miR-424 prominently decreased ramified Iba-1-positive microglia and Iba-1 protein levels, and, meanwhile, reduced the TNF-α level in the cortex after 8-hour ischemia. Moreover, in vitro study showed that miR-424 mimics reduced the activation of BV2 microglial cells and decreased mRNA level and release of TNF-α.…”
Section: Discussionmentioning
confidence: 79%
“…According to existing studies, inflammatory mediators synthesized in microglia upon activation contribute largely to ischemic brain injury, promoting neuronal death in the penumbra and the progression of penumbra into ischemic infarction [42,43] . The phosphorylation and activation of p38 is of particular importance in regulating the production of inflammatory mediators induced by hypoxia [44,45] .…”
Section: Discussionmentioning
confidence: 99%